Role of the neuroendocrine complex in immunotropic effects of nitrogenous metabolites in rats - Igor Kuchma; Anatoliy Gozhenko; Igor-Severyn Flyunt; Sofiya Ruzhylo; Galyna Kovalchuk; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2021)
Background. We have previously shown that nitrogenous metabolites have immunomodulatory effects, both suppressor and enhancing, both in healthy rats and in humans exposed to pathogenic influences. The immunomodulatory effect of bilirubin is probably mediated through aryl hydrocarbon receptors, and uric acid through TL- and adenosine receptors of immune cells. The question of mediators of the immunomodulatory action of urea and creatinine remains open. We hypothesized the mediating role of mediators of the autonomic nervous system and adaptive hormones. The aim of this study is to analyze the relationships between the parameters of nitrogenous metabolites and the parameters of the autonomic nervous and endocrine systems, on the one hand, and between neuroendocrine and immune parameters - on the other hand. Material and methods. Experiment was performed on 60 healthy female Wistar rats. The plasma levels and urinary excretion of the nitrogenous metabolites, HRV and endocrine (corticosterone, triiodothyronine and testosterone plasma levels, calcitonin, parathyroid and mineralocorticoid activities, the thickness of glomerular, fascicular, reticular and medullar zones of adrenals) parameters as well as parameters of immunity were determined. Results. According to the results of canonical correlation analysis, the modulating effects of nitrogenous metabolites on neuroendocrine parameters are quite pronounced and almost identical in terms of bilirubin (R=0,603), creatinine (R=0,602), uric acid (R=0,599) and urea (R=0,586). Taken together, nitrogenous metabolites determine neuroendocrine parameters by 71,5% (R=0,845; χ2(84)=179; p<10-6). Triiodothyronine, fascicular and medullar areas of the adrenal glands, vagal tone and calcitonin activity were the most susceptible to nitrogenous metabolites. In turn, neuroendocrine parameters determine the parameters of immunity, subject to exposure to nitrogenous metabolites, by 95,8% (R=0,979; χ2(264)=405; p<10-6). Conclusion. Previously identified immunomodulatory effects of nitrogenous metabolites are realized, perhaps, through the factors of the autonomic nervous and endocrine systems.